PSV-32 Influence of chlorate and chlorate plus molybdate on the growth of multi-drug resistant staphylococci. (5th December 2019) - Ruiz, Oscar; Castillo-Castillo, Yamicela; Anderson, Robin; Hume, Michael E; Arzola, Claudio; Felix, Monserrath; Olivas, Ana Luisa; Armendariz, Ruth; Carlos, Leonardo; Salinas-Chavira, Jaime
Abstract: This study was conducted to determine the effects of chlorate, a metabolic precursor of the bactericide chlorite, when administered without or with molybdate, an essential component of a co-enzyme contributing to nitrate reductase conversion of chlorate to chlorite, against methicillin-resistant staphylococci, important mastitic-pathogens of livestock. Two methicillin-resistant Staphylococcus aureus (strains CP and 49521) were individually cultured for 12 h at 39 o C in nitrate-supplemented (5 mM) ½-strength Brain Heart Infusion broth (10 mL/tube) treated without (control) or with 5 mM chlorate (CL) or 5 mM chlorate plus 1 mM molybdate (CLMO). Control and treated cultures were incubated anaerobically in triplicate and growth was measured via absorbance at 600 nm. An analysis of variance revealed an inhibitory effect of treatments (P < 0.05) on maximum absorbances observed after the 12-h incubation, with maximum absorbances for CP (1.22, 0.10, and 0.46; SEM = 0.12) and 49521 (1.24, 0.22 and 0.06, SEM = 0.09) being higher in controls than in CL- and CLMO-treated cultures, respectively. Similarly, mean specific growth rates of S. aureus CP and 49521 were inhibited (P < 0.05) by both treatments during the first 6 h of growth, with rates being most rapid in control cultures, intermediate in CLMO-treated cultures and slowest in CL-treated cultures (0.68, 0.27 and 0.03 h -1, SEM= 0.15; and 0.92, 0.47 and 0.09 h -1, SEM = 0.08; for CP and 40521, respectively). Growth rates did not differ (P > 0.05) between controls or treatments during the last 6 h of incubation, averaging 0.74 and 0.75 h -1 for both CP and 49521 (SEM = 0.20 and 0.22, respectively). These results confirm that chlorate treatment inhibits methicillin-resistant Staphylococcus aureus strains CP and 49521 although moderate adaption by these strains began to occur after 6 h incubation which, contrary to expectation, was not overcome by co-treatment with molybdate.